Professionalism Level of Agricultural Extension in Karo and Samosir Regency - Helena Tatcher Pakpahan; Ravik Karsidi; Sugihardjo Sugihardjo; Sapja Anantayu (AIBPM Publisher, 2022)
Professionalism is a person competent at work, trusted, has character, is ethical, communicative, and can work together. Professional agricultural extension is required to have good abilities, namely character, conceptual, technical, contextual, communication, adaptive, anticipatory, and cooperative. The aim is to determine the level of professionalism of agricultural extension workers. The professionalism of agricultural extension from four perspectives, namely (1) philosophical orientation; (2) development orientation; (3) characteristic orientation and (4) non-traditional orientation. The research sample was agricultural extension workers in Karo and Samosir regency. The number of research samples is 174 extension workers. The data is presented in a frequency and percentage table with categories 1 to 3. Categorization is based on the value of the mean interval and standard deviation of each sub-variable, namely: low category, medium category and high category. The result is that the level of professionalism of the extension workers is (1) the philosophical orientation sub-variable has a value in the high category of 44.3%; (2) the development orientation sub variable has a moderate category value of 46%; (3) the characteristic orientation sub variable has a low category value of 45%, and (4) the non-traditional orientation sub-variable has a low category value of 47%.Keywords: Agricultural, Agricultural extension, Karo regency, Samosir regency Professionalism.